Conceptual Disaster Management in Regional Policy Analysis - Hayu Nawang; Ernalem Bangun; Arief Budiarto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Disaster management is one of the government's efforts to protect the community from disaster hazards. For this reason, in terms of disaster management that has occurred in disaster-prone areas so far. The role of the local government bureaucracy is often less relevant between the rules and the implementation that occurs in the field. As a result, there is a clash between the interests of the community, inter-regional interests, and inter-agency interests, so the role of the local government bureaucracy becomes less optimal and less effective, which has an impact on not paying attention to public awareness to be independent in dealing with natural disasters. The purpose of this research is to describe conceptual disaster management and regional policy analysis. The method used is a qualitative method with a descriptive approach through literature study. Based on the results of the research, it can be understood that a Disaster Management System is an integrated disaster management implementation system covering aspects of legislationregulation, planning, institutional and funding, as well as the implementation of disaster relief. The conceptual disaster management that needs to be strengthened for the disaster management system includes Pre-Disaster, Emergency Response, and Post-Disaster. Thus, in analyzing the policy there are interconnected factors between one another and their implementation in the field must go hand in hand. Improve institutional and community readiness in preventing, facing, and overcoming natural disasters that will occur, (prioritizing disaster risk reduction as a national priority with strong institutions, identifying, assessing, monitoring disasters and implementing early warning systems, and disaster management and increasing disaster preparedness.